The USA Poster in the 1890’s. The Issues of the Origins and the General Peculiarities of the Journal Poster - Petukhova, Elena A. (Actual Problems of Theory and History of Art, 2013)
The article is devoted to the issue of American poster of the 1890’s. Despite that this issue takes an important place in the worldwide history of the poster art, now it is a little-explored domain for the research. In the paper are considered such problems as the origins of the poster in the USA, its main characteristics and also here is presented an analysis of the several graphic works.
Keywords: poster; graphic; engraving; graphic design; the USA; Will Bradley; Edward Penfield; Louis Rhead